A Model for Peer Experiential and Reciprocal Supervision (PEERS) for Genetic Counselors: Development and Preliminary Evaluation Within Clinical Practice. Issue 2 (25th September 2012) - Sexton, A.; Hodgkin, L.; Bogwitz, M.; Bylstra, Y.; Mann, K.; Taylor, J.; Hodgson, J.; Sahhar, M.; Kentwell, M.
Abstract: A model for practising genetic counselors to obtain clinical supervision via reciprocal peer observation and feedback was developed and trialled. The model was developed in response to a perceived lack of opportunity for immediate observational feedback for practising genetic counselors. The aims reached by consensus were to facilitate learning new approaches and skills, to revitalise current ways of practising, and to enhance supervision skills in a two‐way process, where the observer learnt from the counselor, and vice‐versa. The genetic counselors agreed on a process of paired reciprocal observation whereby the observer was present in the room during the counseling session, and a reflective feedback discussion was arranged within 24 h of the session. Four main themes emerged from analysis of the recorded discussions were (i) "I wasn't sure if I‐": voicing of doubts or internal questions that occurred during session for the counselor conducting the session, (ii) "I really liked that": positive feedback and validation from the observer, (iii) "I wonder whether‐": offering of alternative views, insights and strategies by the observer, and (iv) "That's a real thing for me to take away and think about": evidence of learning by both observers and counselors.